TINJAUAN YURIDIS PENETAPAN LOKASI PADA PENGADAAN TANAH DALAM SKALA KECIL - Rachmatika Lestari; Safrida Safrida; Phoenna Ath Thariq; Yuhdi Fahrimal (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
Land acquisition is a way to acquire land for development in the public interest. Land acquisition arrangements in Law Number 2 of 2012 concerning Land Procurement for Development in the Public Interest. Article 1 number 2 of the law stipulates that: "Land acquisition is an activity of providing by giving appropriate and fair compensation to the rightful parties”. With the spirit of efficiency and effectiveness, based on Article 53 paragraph (1) Regulation of the Head of BPN Number 5 of 2012 which states that for the procurement of land with an area of no more than 1 (one) hectare, it can be done directly by the Agency which requires land with the Rightful Party, by buying and selling or exchanging or other methods agreed by both parties then amended to 5 (five) hectares with the issuance of Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 6 Year 2015. Based on the description that has been stated, the formulation of the problem that will be discussed in this paper is whether there can be a consignment in small-scale land acquisition if there is no location determination? This research is a normative juridical research. This research is focused on examining the application of rules or norms in positive law. The data source used in this study is secondary data, which is done by examining library materials, or laws and regulations. The results showed that the location of land acquisition on a small scale can also be determined. This is because there is the word "can" in Article 121 paragraph (1) of Presidential Regulation No. 148 of 2015 which means that the determination of location can be done and may not be done in small-scale land acquisition. Therefore, in order for the consignment to be registered by the court, even in the small scale land acquisition, location determination can be made as one of the requirements for registration of the application to the court.Keywords: land acquisition, small scale land acquisition, consignment